Analisis Terhadap Peluang dan Strategi Pengembangan Ide Bisnis DIY Charm di Indonesia - Mohammad Afrizal miradji; Bayu Adi; Tania Eka Sabrina; Ratu Aimartasia; Dwi Helena Yuliastari; Galang Trian Saputra; Abiansyah Abiansyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze market opportunities and development strategies for the DIY Charm business idea in Indonesia. The growing interest in creative products that emphasize personalization and emotional value has created significant potential for DIY Charm to develop as part of the creative industry. This research employs a descriptive qualitative approach using literature review, observation, and strategic analysis through SWOT and Business Model Canvas frameworks. The findings indicate that DIY Charm benefits from strong market opportunities driven by consumer lifestyle trends, digital platform utilization, and the increasing role of UMKM in the national economy. Product differentiation, branding consistency, digital marketing strategies, and community engagement emerge as key factors in supporting business growth. The study highlights that a well-structured business model and adaptive strategy are essential for maintaining competitiveness and long-term sustainability. The results are expected to serve as a reference for entrepreneurs and stakeholders in developing creative business ideas that align with market dynamics in Indonesia.